2009
DOI: 10.1080/15391523.2009.10782546
|View full text |Cite
|
Sign up to set email alerts
|

Student Teachers’ Intentions and Actions on Integrating Technology into Their Classrooms during Student Teachings

Abstract: The purpose of the study is to explore student teachers' intentions and actions in technology integration in their classrooms. A postgraduate teacher education cohort of 118 Singapore stvAent teachers participated in the study. The results suggested that student teachers in Singapore showed positive intentions to integrate technology to facilitate student-centered learnin[ in their fumre teaching. However, they reported that they were more likely to use technology as :1. supporting and instructional tool durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
2
34
1
7
Order By: Relevance
“…Other plans include developing a measure for behavior that will capture whether or not the preservice teachers actually choose to use technology when given the choice during student teaching. Other studies (Choy, Wong, & Gao, 2009) have concluded that more studies are needed to examine how intention translates into practice in the real-life classroom and therefore we would propose visiting teachers once employed. Observations and documentation of actual classroom use would likely provide the technology integration research community a more robust predictive model to better shape preservice curricula and design more appropriate learning experiences in increase teacher technology use in the future.…”
Section: Significance Of Study and Limitationsmentioning
confidence: 99%
“…Other plans include developing a measure for behavior that will capture whether or not the preservice teachers actually choose to use technology when given the choice during student teaching. Other studies (Choy, Wong, & Gao, 2009) have concluded that more studies are needed to examine how intention translates into practice in the real-life classroom and therefore we would propose visiting teachers once employed. Observations and documentation of actual classroom use would likely provide the technology integration research community a more robust predictive model to better shape preservice curricula and design more appropriate learning experiences in increase teacher technology use in the future.…”
Section: Significance Of Study and Limitationsmentioning
confidence: 99%
“…With respect to the impact of technology on the concretization of concepts, Hannafin and Land (1997) commented: "Technology-enhanced, student-centered learning environments often facilitate understanding of abstract concepts via concrete experience". The pre-service teachers included in the study by Chay, Wong and Gao (2009) showed confidence in their technology skills and felt that integrating technology would enhance their students' learning experiences. Also according to the views of the pre-service teachers at the department of classroom teaching included in the study by Yavuz and Coşkun (2008), the use of technological tools and materials in courses has many benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains many studies that emphasize the importance of the integration of technology into education and into the learning process (Duran, Brunvand, & Fossum, 2009;Chay, Wong, & Gao, 2009;Tor & Erden, 2004;Keeler, 2008;Smolin & Lawless, 2011). According to Bell (2011), learners, teachers and managers are trying to integrate technology into learning in formal and informal settings.…”
Section: Introductionmentioning
confidence: 99%
“…Öğretmen yetiştirme programları çerçevesinde öğretmen adaylarının BİT entegrasyon becerilerinin geliştirilerek entegrasyon sürecine hazır olmalarını sağlamak önemlidir (Choy, Wong ve Gao, 2009;Dawson, Forster ve Reid, 2006;Niess, 2005). Ancak yeni nesil öğretmen eğitiminin öğretmen adaylarını gelecekte BİT kullanımına teşvik ettiği görülse de, öğretmen eğitiminde yer alanların bu süreci BİT'in değişim hızıyla orantılı olarak dinamik bir şekilde tasarlamaları, değerlendirmeleri ve sürekli olarak yeniden düzenlemeleri gerekmektedir (Chai, Koh ve Tsai, 2010).…”
Section: Sonuçlarunclassified
“…Bunun bir sonucu olarak öğretmen adaylarının oluşturdukları bu inanç göreceli olarak değişime de dirençli olabilmektedir (Hermans, Tondeur, Van Braak ve Valcke, 2008;Ertmer, 2005). Bu çerçevede öğretmen yetiştirme sürecinde görev alanların, öğretmen adaylarının BİT'İ entegre etmeye hazır olmalarını sağlamak için BİT entegrasyon becerilerini geliştirmenin yanı sıra öğretmen adaylarının bunu başarabileceklerine ilişkin düşünce ve inançlarına da odaklanmalarına gereksinim vardır (Chen, 2010;Choy, Wong ve Gao, 2009;Brownlee, Purdieve Boulton-Lewis, 2001). …”
Section: Introductionunclassified